Tona, the Folk Healing Practices in Rural Punjab, Pakistan - Azher Hameed Qamar (Journal of Ethnology and Folkloristics, 2016)
Consulting religion and magic for healing is an important aspect of healing belief practices. Magical thinking provides space for culturally cognitive patterns to integrate belief practices. Tona, a layman’s approach to healing that describes magico-religious (fusion of magic and religion) and secular magic practices in rural Punjab, Pakistan, is an example of magico-religious and secular magical practice. The purpose of this study is to analyse tona as it is practiced to cure childhood diseases (sokra and sharwa) in Muslim Punjab, Pakistan. This is an ethnographic study I conducted using participant observation and unstructured interviews as the primary research methods. The study produced an in-depth analysis of tona as a healing belief practice in the light of Frazer’s principles of magical thinking and sympathetic magic. The study provides a deeper understanding of the magical thinking in magico-religious healing belief practices.